THE DECADAL CHANGES AND SOCIO-ECONOMIC STRESSES ON COASTAL AREA THROUGH REMOTE SENSING AND GIS TECHNOLOGY: A REVIEW OF PURI, ODISHA (International Association of Biologicals and Computational Digest, 2022)
Coastal areas of Odisha are vulnerable to climate change. Along the 480 km coastline most of the coastal areas are facing threats due to climate change. In addition to threats due to natural hazards, these coastal regions also face immense population and developmental pressures. The increase in the intensity and frequency of cyclones and accelerated sea level rise related to increased sea surface temperature have led to flooding, coastal erosion and shoreline retreat causing damage to coastal ecosystems and resources in these regions. Coastal areas are the key system for global sustainability. Coastal regions gained importance because of multiple uses, like high productivity of the ecosystem, highly concentrated population, industrial friendly, waste disposal, tourism, transportation, strategic planning in military and many more. These coasts are always in a dynamic state trying to change, and nature always works for maintaining the equilibrium. In this scenario, coastal management has become the important issue in past few decades. Thus, coastal vulnerability assessment methods have been developed to identify and manage vulnerable areas over the coast. In recognition to these risks, the present review, the main focus is on the coastal area of Puri beach- the Ballighai beach which is very close to Jagannath Mandir and Swargdwar. Proper planning with awareness and protection strategies for Indian coast must be taken swiftly by the coastal management and policymakers to safeguard coastal ecosystem and livelihoods. In recent years, there has been much focus on the coastal vulnerability assessments using various kinds of data. Most of the reported studies over Indian coast are based on Remote Sensing and GIS methods. Thus this review tries to explain the importance of remote sensing and GIS in estimating the effects of changing climate on coastal areas.
Keywords: Latex, Aqueous extract, Methanolic extract and Phytochemical constituents